(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Across existence, networks limited by geology, philosophy, language and profound way have over and over made actual constructions to address their aggregate awareness. Pretty much every compositional design addresses, from an immediate perspective, social personality and reasoning inside an actual setting. Sikhism, one of the most youthful of world’s religions, gets its motivation from a living otherworldly and chronicled custom. Master Nanak, the primary Sikh Guru, experienced both Hindu and Muslim religions and it was solely after profound consideration that he advanced his own way of thinking or another administration. There is exceptionally restricted writing accessible regarding the matter of Sikh Architecture. Besides, the writing accessible is principally worried about the authentic portrayal and next to no has been expounded on the Architecture of the Sikh places of worship. Subsequently, it is hard to accept that such a style of design exists by any means. The vast majority of the creators have recently taken up the design of the Harmandar Sahib (Golden Temple) as a contextual investigation for comprehension and clarifying the Sikh engineering in general. Just PS Arshi has examined the instances of some other Gurudwaras, however the examination of different design components of the Sikh engineering has not been concentrated by him. Along these lines, there is a critical need to grow and refresh the examination done by PS Arshi by covering other generally significant Gurudwaras just as to take up an indepth investigation of design components of the Sikh Gurudwaras. 45 Sikh Shrines in East Punjab (Indian Punjab) has been concentrated over the span of study. Since little work has been distributed on the Sikh design, the current work may end up being a spearheading exertion by an engineer and of an incredible worth to the researchers of different fields too.